(3haGb Gdeaghe aj GNJdGa Gdebhd hGdehShes - (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s ((3CMeO Hf CHj HcQ Hf YHO GdQMef GdTgjQ HGHf QRjf GdebOSi GdMfHdi GdYeQi s)
(3ChdgG (B:s
(3CeG HYO MeO Gdgd GdPi dGeMUi dfYeg hPdc Cf ef eSJXQa GdcdGe GdeTZha Hg Phh GdCagGe cdeGJ jhef ajgG GdMQja eY hbhY bGQFjgG ai GdJUMja cbQGAI GdHGA JGA s
(3BNQgG (B:s
(3hGdeTHd hGdeTHi GdYGWa Ydi Cgd Ch UGMH jbGd CTHd Ydjg hCTHi HeYfi YWa hGdgd SHMGfg hJYGdi CYde Je GdcJGH HYhf Gdedc GdhgGH hGdMeO ddg hMOg s
(3CgOGg GdeDda ddfGUQ UdGM GdOjfs
(3HgG fXGe GdJYbjHIs
(3HBNQgG aGFOIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GddZIs